2020
DOI: 10.1093/ageing/afaa020
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness as a mediator of the impact of social isolation on cognitive functioning of Chinese older adults

Abstract: Abstract Background and Objective older adults have increased risk of social isolation, loneliness and cognitive functioning impairment, but the relationships among these factors are not conclusive. We investigated the potential mediation mechanism of loneliness on the association between social isolation and cognitive functioning among Chinese older adults within their cultural context. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 28 publications
3
64
0
2
Order By: Relevance
“…12 And while these are two distinct entities that are inherently difficult to study, literature suggests that they are related, just not directly overlapping. 13 The prevalence of loneliness is difficult to understand, and a variety of tools have been developed to assess for loneliness including the de Jong Gierveld (dJG) Loneliness scale and UCLA Loneliness scale. 14,15 Perissinotto et al showed that 29% of respondents over 75 years old were lonely, while the American Association of Retired Persons (AARP) found about 25% of respondents over 70 years old were lonely; both using the UCLA Loneliness Scale.…”
Section: The Realitymentioning
confidence: 99%
“…12 And while these are two distinct entities that are inherently difficult to study, literature suggests that they are related, just not directly overlapping. 13 The prevalence of loneliness is difficult to understand, and a variety of tools have been developed to assess for loneliness including the de Jong Gierveld (dJG) Loneliness scale and UCLA Loneliness scale. 14,15 Perissinotto et al showed that 29% of respondents over 75 years old were lonely, while the American Association of Retired Persons (AARP) found about 25% of respondents over 70 years old were lonely; both using the UCLA Loneliness Scale.…”
Section: The Realitymentioning
confidence: 99%
“…It is important to observe that one of the mechanisms by which isolation may have an impact on the psychological aspects of an individual is through the role of loneliness as a mediator. This has been demonstrated, for example, in older adults, where the effect of social isolation on cognitive function decline was found to be influenced by the indirect effect of loneliness [21]. This means that, even if constrained within a context of isolation, if a person can maintain social relations and cope with feelings of loneliness, this can potentially mitigate the impact on mental health.…”
Section: Discussionmentioning
confidence: 93%
“…In addressing the objective and subjective aspects of social disconnectedness, it is plausible to hypothesize that the effect of social isolation on cognitive health may be mediated through the subjective feelings of loneliness. Using a sample of community-dwelling older adults in China, Yang and colleagues [13] provided support for this mediation model by demonstrating that the indirect effect of social isolation on cognitive function through loneliness was significant. Given that their study used a set of binary items to construct a latent variable of social isolation and a single item to represent loneliness, the mediation model needs to be revisited with the employment of psychometrically sound multi-item scales for social isolation and loneliness.…”
Section: Introductionmentioning
confidence: 96%
“…We also explore whether the potential mediating role of loneliness in the relationship between social isolation and cognitive health holds across the objective and subjective measures of cognitive impairment. Covariates were selected based on the literature on social disconnectedness and cognitive health in older adults in general and immigrants in particular, and they include sociodemographic characteristics (age, gender, marital status, education, and perceived financial status), immigration-related characteristics (length of stay in the U.S.), and physical and mental health status (chronic medical conditions and depressive symptoms) [6,7,12,13,18,23]. Inclusion of chronic medical conditions and depressive symptoms is in line of the literature demonstrating the interconnectedness among physical, mental, and cognitive health [17,24].…”
Section: Introductionmentioning
confidence: 99%